Improving Physical Education Skills with the Blended Learning Method - Manullang, Frengky Natanael; Girsang, Suranta Juli Kipli; Hasibuan, Marto Perdinan; Siadari, M Rafael; Nurkadri, Nurkadri (CV. Rayyan Dwi Bharata, 2024)
Many students only have expertise in one sport and there are also those who are just learning a particular sport. As a result, they lack understanding and face difficulties when learning. Where sports lessons only concentrate on psychomotor and affective aspects in their implementation. Effective and efficient learning methods will overcome problems and help students achieve learning goals. Combining face-to-face or conventional learning with offline and online learning (Blended Learning) is expected to solve sports learning problems.